PENGARUH JENIS PUPUK ORGANIK PADA PEMBIBITAN TANAMAN KOPI (Coffee sp) - Diah Eka Puspita; Khumaira Khumaira (Fakultas Pertanian, Universitas Syiah Kuala, 2020)
Abstract This study was to determine the effect of adding several types of organic fertilizers to the nursery media for coffee plants. It is expected that data will be obtained that can describe the growth of coffee plant seeds (Coffee sp) well so that superior coffee plant seeds will be produced. The method used was an experimental method using a non factorial randomized block design consisting of 4 planting media treatments that were repeated 3 times. As a growing medium used land (M0); soil + vermicompost (M1); soil + quail dung (M2) and soil + biochar (M3). The parameters observed were, wet weight and dry weight of the plant and root canopy ratio. The nursery was carried out for 5 months. In the parameters of wet weight and plant dry weight analysis of variance showed that media treatment had a very significant effect, namely on the M1 treatment. Whereas the root canopy ratio parameters did not show any effect, although the M1 treatment tended to show the lowest root canopy ratio, which means that the seedlings of this plant had an indication of a better root system.